2015
DOI: 10.1111/jcmm.12475
|View full text |Cite
|
Sign up to set email alerts
|

Blood markers of oxidative stress predict weaning failure from mechanical ventilation

Abstract: Patients undergoing mechanical ventilation (MV) often experience respiratory muscle dysfunction, which complicates the weaning process. There is no simple means to predict or diagnose respiratory muscle dysfunction because diagnosis depends on measurements in muscle diaphragmatic fibre. As oxidative stress is a key mechanism contributing to MV-induced respiratory muscle dysfunction, the aim of this study was to determine if differences in blood measures of oxidative stress in patients who had success and failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
(51 reference statements)
0
6
1
Order By: Relevance
“…Fourth, low albumin can be resulted from hem dilution when fluid overload occurs. (21) However, in spite of all these previous causes of the importance of albumin level in weaning outcome, our results did not show any statistically difference between our three groups of weaning which can be explained by the low level of serum albumin in most of the studied patients of our three groups from the start. As regard liver function test (ALT, AST) was significantly high patients with simple weaning and difficult weaning this can be explained as result of inadequate oxygen uptake by the centrilobular hepatocytes resulting in necrosis.…”
Section: Discussioncontrasting
confidence: 82%
“…Fourth, low albumin can be resulted from hem dilution when fluid overload occurs. (21) However, in spite of all these previous causes of the importance of albumin level in weaning outcome, our results did not show any statistically difference between our three groups of weaning which can be explained by the low level of serum albumin in most of the studied patients of our three groups from the start. As regard liver function test (ALT, AST) was significantly high patients with simple weaning and difficult weaning this can be explained as result of inadequate oxygen uptake by the centrilobular hepatocytes resulting in necrosis.…”
Section: Discussioncontrasting
confidence: 82%
“…Previous studies also reported that cough peak flow was a predictor of reintubation. 24 Fourth, low albumin can be resulted from hemodilution when fluid overload occurs. Patients with cough peak flow 90 L/ min had a very low reintubation rate (1.9%).…”
Section: Discussionmentioning
confidence: 99%
“…23 And systematic inflammation is a risk factor for weaning failure. 24 Fourth, low albumin can be resulted from hemodilution when fluid overload occurs. 25 And a previous study has reported that fluid overload was a risk factor for reintubation.…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance of the intestinal redox status usually restrains the capacity of eliminating ROS, resulting in oxidative damage to the intestinal epithelial cells [23,24]. In addition, MDA is one of the lipid peroxide metabolites and an essential symbol of oxidative damage, which can be enhanced with weaning stress [25,26]. In this study, the higher MDA content with less antioxidant enzymes activity in weaned young goats was expected, which suggests that early weaning can induce oxidative damage in the young goats.…”
Section: Discussionmentioning
confidence: 59%